Bridging the Gap: From Model Surfaces to Nanoparticle Analogs for the Selective Oxidation and Steam Reforming of Methanol and for Selective Hydrogenation Catalysis. - Boucher, Matthew. (2017)
Abstract: Most industrial catalysts are very complex, comprising of non-uniform materials with varying structures, impurities, and interaction between the active metal and supporting substrate. A large portion of the ongoing research in heterogeneous catalysis focuses on understanding structure-function relationships in catalytic materials. In parallel, there is a large area of surface science research focused on studying model catalytic systems for which structural parameters can be tuned and measured with high precision. It is commonly argued, however, that these systems are oversimplified, and that observations made in model systems do not translate to robust catalysts operating in practical environments; this discontinuity is often referred to as a "gap." The focus of this thesis is to explore the mutual benefits of surface science and catalysis, or "bridge the gap," by studying two catalytic systems in both ultra-high vacuum (UHV) and near ambient-environments. The first reaction is the catalytic steam reforming of methanol (SRM) to hydrogen and carbon dioxide. The SRM reaction is a promising route for on-demand hydrogen production. For this catalytic system, the central hypothesis in this thesis is that a balance between redox capability and weak binding of reaction intermediates is necessary for high SRM activity and selectivity to carbon dioxide. As such, a new catalyst for the SRM reaction is developed which incorporates very small amounts of gold (<1 atomic %) supported on zinc oxide nanoparticles with controlled crystal structures. The performance of these catalysts was studied in a fixed-bed micro-reactor system at ambient pressures, and their structure was characterized by high-resolution microscopic and spectroscopic techniques. Pre-existing oxygen defects in zinc oxide {0001} surfaces, and those created by a perturbation of the defect equilibrium by addition of gold, provide an anchoring site for highly dispersed gold species. By utilizing shape control of zinc oxide supports, it is found that highly dispersed gold, capable of low-temperature redox behavior is most prominent on zinc oxide {0001} surfaces and leads to high SRM activity and selectivity to carbon dioxide. Like other Group IB metal catalysts the SRM over gold-zinc oxide proceeds through the formation and weak binding of formaldehyde, and subsequent coupling with methoxy to produce methyl formate. Mechanistic clarification of this point was achieved by studying the interaction methanol-water mixtures with model catalyst surfaces. Model catalysts were studied in a UHV chamber where the base pressure was maintained at 10-10 mbar. High resolutions surface science techniques show that hydrogen-bonded networks of water are capable of deprotonating methanol to methoxy on low index surfaces in the absence of atomic oxygen. These UHV studies show that adsorbates, other than oxygen, are capable of activating methanol on Group IB metal surfaces. The second reaction involves the selective hydrogenation of alkynes to alkenes. Selective hydrogenations of carbon-carbon multiple bonds are important for a wide range of industrial processes. The governing hypothesis for this reaction system is that cooperation between a minority metal with a low barrier for hydrogen dissociation, and a less-reactive host metal capable of hydrogen uptake via spillover will lead to high alkene selectivity. A strategy for the preparation of such a catalyst is developed using model catalyst studied in a UHV chamber. The model catalyst features isolated palladium atoms in a copper(111) surface, termed single atom alloy (SAA). Individual, isolated palladium atoms act as sites for hydrogen uptake, dissociation, and spillover onto an otherwise inert copper(111) host. Weak binding offered by copper provides a surface where selective hydrogenation reactions can take place. Palladium-copper SAA model catalysts are highly selective to the partial hydrogenation of acetylene, whereas surfaces containing larger palladium ensembles facilitate complete hydrogenation and decomposition. Nanoparticle analogs of palladium-copper SAAs were prepared to investigate the feasibility of this strategy for practical application. Very small amounts of palladium (<0.2 atomic %) on the surface of copper nanoparticles are highly active and selective catalysts for the partial hydrogenation of phenylacetylene to styrene. The performance of these catalysts was studied in a liquid-phase, stirred-tank batch reactor under a hydrogen head pressure of approximately 7 bar. Palladium alloyed into the surface of otherwise inactive copper nanoparticles shows a marked improvement in selectivity when compared to monometallic palladium catalysts with the same metal loading. This effect is attributed hydrogen spillover onto the copper surface. In summary, the development of new, highly active and selective catalysts for the methanol steam reforming reaction and for the partial hydrogenation of alkynes to alkenes was accomplished by the use of state-of-the-art techniques in both surface science and heterogeneous catalysis. The implications of this work can be extended to a wide variety of catalytic systems.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Maria Flytzani-Stephanopoulos.; Committee: Charles Sykes, Howard Saltsburg, Terry Haas, and Gary Haller.; Keywords: Chemical engineering, Chemistry, and Materials Science.